Danish Pearyland Expedition, 1947–50 - Troelsen, Johannes C. (Polar Record, 1952)
Peary Land, the northernmost part of Greenland, was until recently among the least known regions of the globe. The coasts are barred by a broad belt of virtually impenetrable pack ice, and the only means of reaching the area in, former times was by dog sledge. The development of air transport in recent years has, however, made possible a more thorough investigation of this remote land.